Analysis of Diplomatic Immunities and Privileges: Case Study of Abuse of Diplomatic Rights by Representatives of North Korean Diplomats - Pangestu, Zeffa Alifah (Journal of ASEAN Dynamics and Beyond, 2022)
In carrying out a diplomatic mission, a diplomatic representative is granted a right of immunity and privileges in order to be able to carry out missions freely. But in practice, there is an abuse of the rights granted. One of them is North Korea's diplomatic representative to Bangladesh, Son Young Nam, who is known to have abused his rights to gold smuggling. This study aims to find out what are the rights of immunity and privileges obtained by diplomatic representatives and what are the legal consequences of the abuse of immunity rights and privileges, with an example of a case study of gold smuggling by a diplomatic representative of North Korea in Bangladesh. The research method used is a qualitative method with primary data obtained through the search results of journals, documents, and official websites. This research uses National Interest Theory in the analysis. This study shows that after diplomatic representatives receive various immunity rights and privileges, then abuse them, there are three ways that the receiving country can choose in responding to the abuse. Such as the declaration of persona non grata, the removal of immunity and privileges, or the termination of diplomatic relations between the two countries as a last resort.